2019
DOI: 10.22146/ijc.44028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyridine Derivative-based Chemosensor for Formaldehyde Detection

Abstract: Compound of 3,3'-(4-(2-amino-4,5-dimethoxyphenyl)pyridine-2,6-diyl)dianiline (CHP) has been synthesized via three-step synthetic procedure from veratraldehyde as starting material and 4-(4,5-dimethoxy-2-nitrophenyl)-2,6-bis(3-nitrophenyl)pyridine (CHP-1) as an intermediate compound. The CHP-1 was reduced using hydrazine hydrate catalyzed by 10% Pd/C to the final target of CHP. The spectroscopic study revealed that CHP in acetonitrile could detect formaldehyde through fluorescence enhancement and showed color c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The increasing intensity and blue shift emission of the fluorescence may be caused by hindering the photoinduced electron transfer (PET) between the imidazole group and the terpyridinyl metal coordinated moiety upon hydroxymethylation of the imidazole, compared with the original imidazole with a 1H−3H annular tautomerism. 29 More importantly, the emission intensity of S1 showed a linear correlation with R 2 = 0.9866 with a slope (k) of 0.1007 over the concentration range of 0.61−8.14 μM HCHO (Figure S66). The LOD of S1 for HCHO against HCHO in aqueous solution was calculated to be 0.75 μM (equivalent to 22.5 ppb) .…”
Section: H Nmr and Esi-ms (Figures S33 And S53)mentioning
confidence: 94%
See 1 more Smart Citation
“…The increasing intensity and blue shift emission of the fluorescence may be caused by hindering the photoinduced electron transfer (PET) between the imidazole group and the terpyridinyl metal coordinated moiety upon hydroxymethylation of the imidazole, compared with the original imidazole with a 1H−3H annular tautomerism. 29 More importantly, the emission intensity of S1 showed a linear correlation with R 2 = 0.9866 with a slope (k) of 0.1007 over the concentration range of 0.61−8.14 μM HCHO (Figure S66). The LOD of S1 for HCHO against HCHO in aqueous solution was calculated to be 0.75 μM (equivalent to 22.5 ppb) .…”
Section: H Nmr and Esi-ms (Figures S33 And S53)mentioning
confidence: 94%
“…S1 concentration-dependent fluorescence titration experiments with formaldehyde are shown in Figure d, where the fluorescence emission intensity of S1 was gradually enhanced as the formaldehyde content increased and the maximum emission wavelength was blue-shifted (556 to 538 nm). The increasing intensity and blue shift emission of the fluorescence may be caused by hindering the photoinduced electron transfer (PET) between the imidazole group and the terpyridinyl metal coordinated moiety upon hydroxymethylation of the imidazole, compared with the original imidazole with a 1H–3H annular tautomerism . More importantly, the emission intensity of S1 showed a linear correlation with R 2 = 0.9866 with a slope ( k ) of 0.1007 over the concentration range of 0.61–8.14 μM HCHO (Figure S66).…”
mentioning
confidence: 99%
“…A chemosensor based on 3,3 0 -(4-(2-amino-4,5-dimethoxyphenyl) pyridine-2,6diyl) dianiline was synthesized (Figure 65) and found that it could detect formaldehyde through fluorescence enhancement and show the visible color change from yellow to blue. The compound could act as chemosensor for detection of formaldehyde qualitatively as well as quantitatively [91].…”
Section: à2mentioning
confidence: 99%
“…The crude product as solid was obtained from evaporation of the solvent. The solid was recrystallized from water and ethanol as yellow solid (0.11 g, 44%, mp 260-261°C Generally, the procedure to generate the UV-Vis and fluorescence spectra were the same with the previous work by Hidayah et al (2019). The solutions of chemosensor CHA was prepared by dissolving CHA solid in ethanol until it dissolves completely.…”
Section: Synthesis Of 2-(45-dimethoxy-2-nitrobenzylidine) Malononitrmentioning
confidence: 99%
“…Dar et al (2013) used Thin Layer Chromatography (TLC) method for formaldehyde determination but this method was unable to measure formaldehyde of samples in high concentration. Spectrophotometric methods in detection of formaldehyde are divided into colorimetric (Mohr 2003;Wei et al 2019) and fluorometric (Bi et al 2018;Dong et al 2016;He et al 2016;Hidayah et al 2019;Liu et al 2015;Ovianto et al 2017;Roth et al 2015;Song et al 2012;Wu et al 2018;Xu et al 2016;Zhang et al 2018;Zhou et al 2018Zhou et al , 2015. The method has advantages over other methods, namely simpler, easier to handle, cheaper, higher in sensitivity and can be used for routine analysis (Chen et al 2015;Indang et al 2009;).…”
Section: Introductionmentioning
confidence: 99%